Modulating macrophage function to reinforce host innate resistance against Mycobacterium avium complex infection - Park, Hyun-Eui; Lee, Wonsik; Choi, Sangwon; Jung, Myunghwan; Shin, Min-Kyoung; Shin, Sung Jae (Frontiers in Immunology, 2022)
Mycobacterium avium complex (MAC) is the main causative agent of infectious diseases in humans among nontuberculous mycobacteria that are ubiquitous organisms found in environmental sources such as soil, domestic and natural waters. MAC causes pulmonary infections in patients with underlying pulmonary and disseminated disease in patients with acquired immune deficiency syndrome. While the incidence of M. tuberculosis infection has slowed, MAC infection and mortality rates have increased, making it a global health threat. The treatment success rate for MAC infection is not high because of the emergence of drug resistance or side effects due to long-term drug use. Therefore, there has recently been growing interest in the development of host-directed therapy (HDT), which aims to accelerate mycobacterial clearance and reverse lung damage using immune defense as a novel adjuvant strategy to improve the clinical outcome of MAC infection. Innate immune system dysfunction is considered a major factor in MAC infections. Therefore, in this review, we discuss the innate immune responses that contribute to MAC infection by discussing studies on the immune response of macrophages, the main innate immune cells, and the host susceptibility factors in patients against MAC infection We also discuss, as potential HDTs, drugs that can act on the signaling pathway of macrophages that contribute to antimycobacterial activity as part of the innate immune response during MAC infection. This review provides new insights into MAC infection control that modulates and enhances macrophage function, thereby enhancing host anti-microbial activity by proposing potential HDTs through a deeper understanding of the interactions between macrophages and MACs during infection.